Towards frustration of freezing transition in a binary hard-disk mixture - Huerta, A.; Carrasco-Fadanelli, V.; Trokhymchuk, A. (Condensed Matter Physics, 2012)
The freezing mechanism, recently suggested for a monodisperse hard-disk fluid [Huerta et al, Phys. Rev. E, 2006, 74, 061106] is extended here to an equimolar binary hard-disk mixtures. We are showing that for diameter ratios, smaller than 1.15 the global orientational order parameter of the binary mixture behaves like in the case of a monodisperse fluid. Namely, by increasing the disk number density there is a tendency to form a crystalline-like phase. However, for diameter ratios larger than 1.15 the binary mixtures behave like a disordered fluid. We use some of the structural and thermodynamic properties to compare and discuss the behavior as a function of diameter ratio and packing fraction. Механiзм замерзання, який був запропонований недавно для однокомпонентного флюїду твердих дискiв [Huerta et al, Phys. Rev. E, 74, 2006, 061106], узагальнено на випадок еквiмолярної бiнарної сумiшi твердих дискiв. Ми показуємо, що у випадку, коли вiдношення дiаметрiв є меншим за 1.15, то поведiнка параметра глобального орiєнтацiйного порядку бiнарної сумiшi є подiбною до випадку однокомпонентного флюїду. А саме, при збiльшеннi густини дискiв спостерiгається тенденцiя до утворення кристалоподiбної фази. Однак, для вiдношень дiаметрiв бiльших нiж 1.15 вiдмiчається змiна цiєї тенденцiї на поведiнку, характерну для невпорядкованого флюїду. Ми використовуємо окремi структурнi та термодинамiчнi властивостi для порiвняння та обговорення їх поведiнки як функцiї вiдношення дiаметрiв та параметра упаковки.